Effectively Tunable Bandpass Waveguide Filter Based on Incorporation of Coupled Cylindrical Resonators Cut in Half - Kimsis, Karlis; Semenjako, Janis; Shestopalov, Yury V. (Electrical, Control and Communication Engineering, 2020)
A novel mechanically tunable waveguide dielectric filter is presented in this paper. The resonant structure of the filter is made of a rectangular waveguide cavity and an H-plane dielectric cylinder cut in half. The resonating frequency of the proposed structure can be significantly changed by moving two split cylinder parts. The coupling matrix synthesis technique is used to create the required bandpass filter. A drawback of the proposed structure is that the tuning process invokes a mismatch between the feeding structure and the filter. To overcome this drawback, the tuning screws between the coupling irises are used. A filter with the proposed geometry has a large frequency tuning range as well as relatively constant passband bandwidth.